D-dimer levels in patients with nonvalvular atrial fibrillation and acute heart failure treated with edoxaban. Issue 6 (June 2022) - Kida, Keisuke; Nabeta, Takeru; Ishida, Miwa; Shiono, Takaaki; Suzuki, Norio; Doi, Shunichi; Tsukahara, Maya; Ohta, Yuki; Kimura, Tetsuya; Morishima, Yoshiyuki; Takita, Atsushi; Matsumoto, Naoki; et al.
Highlights: Circulating D-dimer levels are a biomarker for ischemic stroke prediction. Patients with acute heart failure and nonvalvular atrial fibrillation have elevated D-dimer levels. Edoxaban may be an effective therapy for keeping D-dimer levels at a lower level. Abstract: Background: D-dimer levels can predict ischemic stroke in patients with acute heart failure (AHF). However, the effects of direct oral anticoagulants on D-dimer levels have not been investigated during admission for AHF in patients with atrial fibrillation (AF). This study examined D-dimer levels immediately after admission and following edoxaban initiation as a sub-analysis of a multi-center study that investigated the pharmacokinetics and pharmacodynamics of edoxaban in patients with nonvalvular AF (NVAF) and AHF. Methods: Hospitalized patients with NVAF and AHF received edoxaban according to the label. The primary measure was the change in D-dimer levels on 7 consecutive days after admission for AHF. We also investigated differences according to prior edoxaban use (de novo at the time of admission or continuation). Results: In 10/13 (76.9%) de novo patients, D-dimer levels exceeded the reference value (1.0 µg/mL) at admission (mean, 2.12 µg/mL) and subsequently decreased in 9 patients (at final blood sampling: mean, 1.12 µg/mL); 1 patient did not fall below the reference value due to stasis dermatitis. In the continuation group, most patients had D-dimer levels below the reference value from Day 1 (mean, 0.93 µg/mL), and levels remained stable or decreased (at final blood sampling: mean, 0.49 µg/mL). No events of stroke were observed. Conclusions: D-dimer levels may be elevated in patients with NVAF and AHF, particularly in those without prior anticoagulant treatment. Edoxaban may be effective for lowering and keeping D-dimer levels, a biomarker for predicting ischemic stroke, below the reference value in patients with NVAF and AHF. Graphical abstract: Image, graphical abstract .